(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The publication presents the results obtained from the study of junior archery performances in the classification rounds. The training of athletes is considered a complex and multi-component process, where there are a large number of efforts of the coach and the athlete, which as a whole must comply with the current rules of competitive activity. The purpose of our study was to determine model performance indicators of junior archers in the classification rounds of major competitions during 2017-2021. The athletes’ performance protocols were analyzed and the best sports results in the qualifying round were highlighted. With the help of theoretical analysis and generalization of data, the state of research of the object and the subject, the concretization of the goal was studied. The calendar plan of competitions of the National Archery Federation, literary sources, researches of scientists conducted in recent years regarding the system of competitions in archery and processes that encourage the improvement of the performance of junior athletes are analyzed. With the help of mathematical statistics methods, an opportunity was created to work out the results that took place on the basis of mathematical statistics methods, where the arithmetic mean, deviation and percentages based on the results of the athletes’ performances in the qualifying round of the competition were determined. The analysis of the protocols of competitive activity made it possible to establish that the athletes’ results are not uniform and are demonstrated under the influence of intense loads. Differences in performance in the qualifying round of the Ukrainian Championships are observed for the category of junior girls in 2018, and a higher density of results was characteristic of junior girls in 2021 and junior boys - 0.39% - in 2017, respectively.